(untitled) (Journal of Economic Research & Business Administration, 2020)
Nowadays, in the competitive environment, to conduct a high-quality audit, auditors try to use any available information. The audit quality depends on the amount of audit risk that determines the efforts of the audit company. In this regard, the task of finding additional factors that have a significant impact on the audit risk evaluation comes to the fore. One of the factors that influence on audit risk evaluation and risk management is the tone of financial reports. Based on the use of content analysis, regression analysis, this article checks whether the linguistic tone used for corporate annual reports is related to the level of audit risk. The model is based on previous studies factors determining audit risk, with the inclusion of new variable characterizing an optimistic or negative report tone. We find that annual reports with positive tone are associated with a lower audit risk, suggesting that the tone of the annual report may be considered as a factor to assess audit risk. In general, the data obtained indicate that auditors can improve their methods of assessing audit risks by systematically taking into account the linguistic qualitative characteristics of financial statement disclosures.